Characteristics of an effective teamwork : Analyzing the role of psychological safety on team effectiveness and performance - Jaakkola, Eveliina Annukka (My University, 2021)
In high-pace and ever-changing business world, organizations rely increasingly more and more on teams, and teamwork has become one of the sought-after business tools for organizations of the 21st century. Organizations create teams and bring together talent in order to achieve competitive edge. However, much of that talent is wasted if people are afraid of speaking up and share their thoughts. Psychological safety refers to an intrapsychic state of how safely and unguardedly individuals can express themselves without a fear of becoming ridiculed, ignored, or compromised. In research literature it has been established that organizations investing and harnessing psychological safety, possess more committed, innovative, and effective personnel, leading to an improvement in several sectors such as performance and well-being. This paper set to explore team psychological safety and its relation on team effectiveness and performance. By interviewing an alliance-based teamwork project, the paper aimed to discover key characteristics of an effective teamwork. By applying Edmondson’s model of Antecedents and Consequences of Team Psychological Safety, the paper aimed to observe the role of team psychological safety. Results reveal three key factors of an effective team: Engaging work climate, workshop training and management, and culture of discussion. Moreover, psychological safety is present in all key factors. Finally, when applying the model, the results strengthen the theory that psychological safety leads to performance improvement. Based on the results, it is encouraged to continue research on team psychological safety in more complex teams as well as remote work teams to further expand on the research.
Keywords: teamwork; group dynamics; safety and security; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Henkilöstöjohtamisen maisteriohjelma|en=Master's Programme in Human Resource Management|